A directional ellipse to describe directional behavior and player activity area in soccer - Fernández-Peña, E.; Castellano, J.; Amatori, S.; Rocchi, M. B.; Sisti, D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
This study aimed to compare four standard deviational ellipse models to assess directional behavior and player activity area in four small-sided games (SSG) of soccer played on pitches with the same width (40 m) and different lengths (30, 40, 50, and 60 m). Fourteen participants played four 7-a-side SSGs on each of the four pitch sizes. Based on GPS data, four ellipse models were calculated for each outfield player and pitch size: major ranges (MR) measuring standard deviation in fixed length and width directions, linear regression assuming length (LRLvsW) or width (LRWvsL) as the independent variable, and principal component analysis (PCA) assuming both length and width as independent variables. Slope, area, semi-major and semi-minor axes, and eccentricity were calculated for each ellipse model. The PCA and LRLvsW models showed similar and valid results for each variable, especially for larger pitch sizes. LRWvsL showed unreliable results. The length axis should be considered as the independent axis when assessing the main direction of players` movements and playing area through a standard deviational ellipse in soccer. This methodology could also be applied to evaluate a team`s labor distribution and spatial distribution of its players.